FAKE POPULARITY FOR REAL MONEY: COMMERCIAL ASTROTURFING AND DATA BUBBLE ON CHINESE DIGITAL PLATFORM - Han, Xiaofei; Hou, Jiaxi (AoIR Selected Papers of Internet Research, 2021)
This on-going research delineates the constructing of an interlocking ecosystem around popularity magnification on popular Chinese digital platforms, which we refer as “data bubble”. Similar to the bubble in a stock market or in real estate market in different economies where the price of assets substantially exceeds its intrinsic value, we propose “data bubble” as a neologism to describe the phenomenon and ecosystem of manipulating data to aim for an inflated popularity on Chinese digital platforms, which ultimately pitch to higher commercial and financial values. We argue that data bubble is laced with platform company’s commercial and financial imperatives, logics of datafication and popularity of platform as data infrastructure, and active participation from different user groups and complementors, and a deeply embedded mentality of “traffic is king”. It is achieved through mixed data practices including data optimization, commercial astroturfing, and counterfeit data manufacturing behind which a wide range of actors and entities are involved. They range from platforms, individual end users (fans in particular), influencers, multi-channel networks (MCNs) and incubators, celebrities and their agencies, click farms, and advertisers—all of them have achieved their own ends and thus actively participated in fabricating data bubble in one way or another. The practices of data manipulating and optimization by different participants in constructing data bubble, as a result, have driven the data metrics on Chinese platforms far over—and no longer representative of—the actual popularity.